Budaya Konsumtif dan Identitas Sosial: Studi Budaya terhadap Perilaku Konsumen Fashion Lokal - Anita Nur Diana; Novita Oktaria (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study examines the relationship between consumerist culture and social identity formation in the consumption of local fashion among urban youth in Indonesia. Employing a qualitative approach with a phenomenological design, data were collected through in-depth interviews with 10 urban consumers of local fashion aged 20–35 years who are active social media users. Thematic analysis revealed four main findings: support for local products, fashion consumption as a representation of identity and social status, the strong influence of social media on consumption preferences, and consumerism as part of everyday lifestyle practices. The results indicate that local fashion consumption is predominantly driven by symbolic motives related to self-image and cultural affiliation, while functional considerations such as comfort and quality remain secondary. This study contributes to cultural consumption studies by highlighting how local fashion serves as a medium for negotiating social identity in the digital era, particularly among urban Indonesian youth.